T4 Diabetes and pseudomonas, a terrible combination? examining the uk cystic fibrosis registry for a sex difference in outcomes (2008–2013). (15th November 2017) - Hippolyte, SS; Simmonds, NJ; Bilton, D; Griesenbach, U; Keogh, R
Abstract : Introduction: FEV1 and BMI are well-validated predictors of disease severity and outcome in cystic fibrosis (CF), however, the impact of sex remains debated. The UK-CF Registry features demographic and clinical information on >99% of the UK-CF population (∼10 000 individuals). Data were used to investigate whether there was a sex difference in change in FEV1 and BMI between 2008–2013, and if this difference could be explained by chronic Pseudomonas aeruginosa (cPsA) infection or CF-related diabetes (CFRD). Methods: Longitudinal analyses (2008–2013) compared male/female age at cPsA acquisition as well as FEV1 and BMI differences between individuals with cPsA infection. Regression analysis examined for a difference in change in BMI and FEV1 between the sexes depending on CFRD and cPsA status, adjusting for age, genotype and ethnicity. A survival analysis completed the sex comparison. Results: Females were significantly younger than males at the time of new cPsA infection (20.9 vs 22.4 years; p<0.001) with a lower mean BMI with new cPsA (21.3 vs 22.2 years; p<0.001) but no difference in FEV1 at time of new cPsA. Females had greater decline in FEV1 than males (8.2% vs 7.0% over 5 years; p<0.001), this was even greater in individuals with cPsA (10.2% vs 8.2% in males:p=0.002). Females had less of an increase in BMI than males (0.2 vs 0.6 in males;p<0.001), this difference was only seen in individuals with cPsA. Sex differences in change in BMI were also seen in the CFRD population. Overall, median survival for females was significantly less than males (39.5 vs 44.2 years, p<0.001). Females with CFRD had the worst survival overall. Males without cPsA had the greatest median survival while males with cPsA had similar survival to females irrespective of their cPsA status. Conclusions: Females had earlier cPsA infection and lower BMI. CPsA was associated with greater decline in FEV1 and BMI in females than males, with worse survival in females with cPsA that was not seen in males with cPsA. CFRD was associated with less BMI increase in females, with females with CFRD having worse survival overall. These data suggest a measurable sex difference in clinically relevant CF outcomes in the UK population.